Experience sharing, emotional reciprocity, and turn-taking - Stevanovic, Melisa; Peräkylä, Anssi (Frontiers in Psychology, 2015)
In this perspective article, we consider the relationship between experience sharing and turn-taking. There is much evidence suggesting that human social interaction is permeated by two temporal organizations: (1) the sequential framework of turn-taking and (2) the concurrent framework of emotional reciprocity. From this perspective, we introduce two alternative hypotheses about how the relationship between experience sharing and turn-taking could be viewed. According to the first hypothesis, the home environment of experience sharing is in the concurrent framework of emotional reciprocity, while the motivation to share experiences is in tension with the sequential framework of turn-taking. According to the second hypothesis, then again, people’s inclination to coordinate their actions in terms of turn-taking is motivated precisely by their propensity to share experiences. We consider theoretical and empirical ideas in favor of both of these hypotheses and discuss their implications for future research.